Dynamic vision training transfers positively to batting practice performance among collegiate baseball batters. (November 2020) - Liu, Sicong; Ferris, Lyndsey M.; Hilbig, Susan; Asamoa, Edem; LaRue, John L.; Lyon, Don; Connolly, Katie; Port, Nicholas; Appelbaum, L. Gregory
Abstract: A growing body of evidence demonstrates visual, perceptual, and oculomotor abilities contribute to batting performance in baseball and there is interest in whether training such abilities can transfer positively to batting performance. The current study tested this question through a pre-registered, randomized, and placebo-controlled intervention, conducted with 24 collegiate baseball players at two NCAA Division 1 universities. Athletes were randomized to receive either dynamic vision training consisting of stroboscopic, anticipatory timing, and eye quickness drills, or placebo drills stylized after control procedures in previous vision therapy studies. Generalized near-transfer was tested via a digital visual-motor task battery ( n  = 20), while sports-specific intermediate and far transfer of training were evaluated through instrumented batting practice metrics ( n  = 14) and box score performance in NCAA-sanctioned games ( n  = 12), respectively. The effects of training group were tested on these outcome measures while controlling for covariates such as pre-training expectations and site. Participants averaged 8.50 hours of training with no significant group differences in training adherence, expectations, or baseline assessments. ANCOVA revealed no group differences in measures of visual-motor skills or NCAA game statistics. However, batting practice demonstrated significant improvements in launch angle ( p  = 0.002, Cohen's d  = 0.74) and hit distance ( p  < 0.001, Cohen's d  = 0.70) for the active training cohort relative to the placebo control. This controlled and pre-registered pilot study therefore provides preliminary evidence that vision training may improve batting practice performance, creating new opportunities for the transfer of skill training and warranting further study. Highlights: Conducted pre-registered, randomized, placebo-controlled training study with baseball batters. Training design guided by the modified perceptual training framework. 24 batters on two college teams received either dynamic or placebo vision training. Causal evidence of training transfer observed in instrumented batting performance. Several alternative explanations for the transfer evidence were ruled out.